The phenomenon of Corruption and its impact on the growing problem of Unemployment in Iraq after a year ( 2003 ). - نصوري, فيصل اكرم; كزار, مصطفى حميد (Journal of Economics and Administrative Sciences, 2014)
Corruption is a phenomenon that exists in all times and places, they appear in the developing countries and in developed countries, and in all political systems. And its repercussions and economic repercussions on the society in which it is rampant, and lead to the undermining of economic development and obstruction, is also working on increasing poverty and unemployment, as well as its role in the worsening of social problems, and political instability. And corruption is deviant behavior is illegal and contrary to the teachings of the religious and moral values. The emergence of this phenomenon is due to several reasons, including political, economic, social and cultural. Which may be internal or external source and this is what leads to serious effects in the structure of economic and social development of States. The spread of the phenomenon of corruption in developing countries, the main reason for the spread of the phenomenon of underdevelopment, which is reflected in all aspects of life, and lead to a waste of economic and financial resources, and the loss of time and effort, which led to the loss of the opportunity to progress and prosperity in these countries. Because of the serious implications of these reports agreed to international organizations and local bodies to fight the phenomenon of corruption in those countries, including the Iraq. That's where corrupt behavior has spread all Iraqi governmental institutions because of what passed by the economic blockade and long wars and occupation of the U.S., leaving significant effects on the behavior of public servants in particular and on the behavior of members of the community to Nhuaam, which contributed to the low rates of investment, both domestic or foreign, Fady to lower investment projects that can accommodate the economically active workforce, That reflected the worsening of unemployment in Iraq.